2013
DOI: 10.2478/s11535-013-0224-7
|View full text |Cite
|
Sign up to set email alerts
|

Hairy roots of Hypericum perforatum L.: a promising system for xanthone production

Abstract: Hypericum perforatum L. is a common perennial plant with a reputed medicinal value. Investigations have been made to develop an efficient protocol for the identification and quantification of secondary metabolites in hairy roots (HR) of Hypericum perforatum L. HR were induced from root segments of in vitro grown seedlings from H. perforatum, after co-cultivation with Agrobacterium rhizogenes A4. Transgenic status of HR was confirmed by PCR analysis using rolB specific primers. HR had an altered phenolic profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 54 publications
3
56
2
1
Order By: Relevance
“…Cyril and Methodius''-Skopje, Republic of Macedonia (MKNH). As for a previous study (Tusevski et al 2013), seeds were washed with 70 % ethanol for 30 s, surface sterilized with 1 % NaOCl for 15 min, rinsed 3 times in sterile deionized water and cultured on MS macro and oligoelements (Murashige and Skoog 1962), B 5 vitamin solution (Gamborg et al 1968), supplemented with 3 % sucrose and solidified with 0.7 % agar. No growth regulator was added.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyril and Methodius''-Skopje, Republic of Macedonia (MKNH). As for a previous study (Tusevski et al 2013), seeds were washed with 70 % ethanol for 30 s, surface sterilized with 1 % NaOCl for 15 min, rinsed 3 times in sterile deionized water and cultured on MS macro and oligoelements (Murashige and Skoog 1962), B 5 vitamin solution (Gamborg et al 1968), supplemented with 3 % sucrose and solidified with 0.7 % agar. No growth regulator was added.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Though naphtodianthrones and acyl-phloroglucinols represent the best investigated groups of metabolites in H. perforatum, there is still an increased demand for further research on flavonoids and xanthones as pharmacologically active compounds (Fotie and Bohle 2006;Nahrstedt and Butterweck 2010). In this view, several studies demonstrated the potential of Hypericum in vitro cultures to accumulate xanthones and their production can be manipulated by the culture type (Pasqua et al 2003), hormonal supplementation (Dias et al 2000), genetic transformation (Tusevski et al 2013) and elicitation (Conceição et al 2006;Franklin et al 2009;Tocci et al 2011). Among the studies for elicitation of H. perforatum cells, Conceição et al (2006) reported strong enhancement of xanthone accumulation upon treatments with Colletotrichum gloeosporioides, methyl jasmonate and salicylic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a lot of recent works on hairy roots induction using plasmid constructions with rol genes and Agrobacterium-mediated method (Bertoli et al 2008, Tusevski et al 2013. Though cloning step of all rol genes is very laborious by reason of large insert size.…”
Section: Biolisticsmentioning
confidence: 99%
“…Previously a different approach of hairy roots formation through single rol gene or rol genes combination was proposed (Spena et al 1987, Cardarelli et al 1987, Vilaine and Casse-Delbart 1987. These rol genes were cloned in binary vectors and were used to transform Agrobacterium tumefaciens strains (Bonhomme et al 2000, Hong et al 2006 which finally infected plant material; co-cultivation plant material with A. rhizogenes strains (Bertoli et al 2008, Tusevski et al 2013, Thilip et al 2015, Rana et al 2016; or biolistic bombardment (Aguado-Santacruz et al 2009). …”
Section: Introductionmentioning
confidence: 99%